Early memory consolidation window enables drug induced state-dependent memory. (1st March 2019) - Osorio-Gómez, Daniel; Saldivar-Mares, Karina S.; Perera-López, Aldo; McGaugh, James L.; Bermúdez-Rattoni, Federico
Abstract: It is well established that newly acquired information is stabilized over time by processes underlying memory consolidation, these events can be impaired by many drug treatments administered shortly after learning. The consolidation hypothesis has been challenged by a memory integration hypothesis, which suggests that the processes underlying new memories are vulnerable to incorporation of the neurobiological alterations induced by amnesic drugs generating a state-dependent memory. The present experiments investigated the effects of amnesic drugs infused into the insular cortex of male Wistar rats on memory for object recognition training. The findings provide evidence that infusions of several amnesic agents including a protein synthesis inhibitor, an RNA synthesis inhibitor, or an NMDA receptor antagonist administered both after a specific period of time and before retrieval induce state-dependent recognition memory. Additionally, when amnesic drugs were infused outside the early consolidation window, there was amnesia, but the amnesia was not state-dependent. Data suggest that amnesic agents can induce state-dependent memory when administered during the early consolidation window and only if the duration of the drug effect is long enough to become integrated to the memory trace. In consequence, there are boundary conditions in order to induce state-dependent memory. Highlights: Anisomycin induces state-dependent recognition memory. DRB, an elongation RNA inhibitor, induces state-dependent recognition memory. The duration of drug action is a boundary condition for the induction of state-dependent recognition memory. Drugs induce state-dependent memory only when infused at early consolidation window.